Optimal Allocation of DSTATCOM in Distribution Network Using Whale Optimization Algorithm - Balamurugan, P.; Yuvaraj, T.; Muthukannan, P. (Engineering, Technology & Applied Science Research, 2018)
This paper deals with a new approach implemented to decrease power losses and improve voltage profile in distribution networks using Distribution STATic COMpensator (DSTATCOM). DSTATCOM location can be determined by the voltage stability index (VSI) and sizing can be identified by nature inspired, recently developed whale optimization algorithm (WOA). To check efficacy, the proposed technique is tested on two standard buses: Indian rural electrification 28-bus and IEEE 69-bus distribution systems. Obtained results show that optimal allocation of DSTATCOM effectively reduces power losses and improves voltage profile.